(untitled) (Research, Society and Development, 2020)
The present study aimed to evaluate the data in the literature on the nutritional status of institutionalized elderly in Brazil. The bibliographic survey was performed in the Lilacs and Scielo databases, considering the following eligibility criteria: studies carried out in LSIEs in Brazil and published in the last 10 years (2008-2018), in which the nutritional status was determined by the Body Mass Index. (BMI). The keywords used were: “elderly”, “nutritional status” and “ILPIs”, researched in combination with boolean operators. From 60 articles found in the search, 10 studies were used to compose this review. The main finding of this study indicates that most institutionalized elderly are malnourished. However, attention is drawn to a clear rise to overweight and obesity in this population. Given this, it becomes evident the importance of implementing nutritional assessment periodically in order to monitor nutritional risks and / or associated comorbidities; as well as direct resources for nutritional care aimed at promoting the quality of life and autonomy of these individuals.